Sämtliche Werke. - Naogeorgus, Thomas (Ausgaben deutscher Literatur des XV. bis XVIII. Jahrhunderts., 2015)
Thomas Naogeorg is one of the most important writers of the Reformation movement; his writings reflect the societal, literary, and spiritual problems of life during the middle of the century of Protestant Reformation. This first complete edition of Naogeorg's works will assure him a place in the literary history of the 16th century. Each of the original Latin texts is supplemented with a German translation.